Supporting factors and barriers in implementing kangaroo mother care in Indonesia - Hadi Pratomo; Uut Uhudiyah; Ieda Poernomo Sigit Sidi; Yeni Rustina; Rulina Suradi; Anne-Marie Bergh; Quail Rogers-Bloch; Reginald Gipson (Indonesian Pediatric Society, 2012)
Background Kangaroo mother care (KMC) was introduced toIndonesia in the 1990s. Since then, KMC has not been widelyimplemented and has not received national policy support.Objective The objectives of this case study were to implementKMC by an intervention that would ultimately benefit tenhospitals in Java, Indonesia, as well as identify supporting factorsand barriers to KMC implementation.Methods An intervention with four phases was conducted inten hospitals. Two teaching hospitals were supported to serve astraining centers, six hospitals were supported to implement KMCand two other hospitals were supported to strengthen existingKMC practices. The four phases were comprised of a baselineassessment, a five-day training workshop, two supervisory visitsto each hospital, and an end-line assessment.Results A total of 344 low birth weight infants received KMCduring the intervention period. Good progress with regards toimplementation was observed in most hospitals between the firstand second supervisory visits. Supporting factors for KMC were thefollowing: support received from hospital management, positiveattitudes ofhealthcare providers, patients, families and communities,as well as the availability of resources. The most common challengeswere record keeping and data collection, human resources and staffissues, infrastructure and budgets, discharge and follow-up, as wellas family issues. Challenges related to the family were the inabilityof the mother or family to visit the infant frequently to provideKMC, and the affordability of hospital user fees for the infant tostay in the hospital for a sufficient period of rime.Conclusion KM C appeared to be well accepted in most hospitals.For an intervention to have maximum impact, it is importantto integrate services and maintain a complex network ofcommunication systems. [Paediatr lndones. 2012;52:43-50).